Use of a novel shockwave trode results in better patient acceptance in awake canine patients treated for musculoskeletal disease - Joseph, Gina L.; Duerr, Felix M.; Zhou, Tianjian; Elam, Lindsay H. (Frontiers in Veterinary Science, 2023)
Extracorporeal shockwave therapy (ESWT) is used as a treatment option for several musculoskeletal pathologies in dogs. When performing ESWT using electrohydraulic devices, sedation is commonly recommended due to the noise and discomfort associated with the treatment. The aim of this study was to compare the tolerance of ESWT delivered by a standard or novel trode in awake canine patients with musculoskeletal disease. Materials and Methods This was a prospective, blinded clinical trial in which dogs with musculoskeletal disease received awake treatment with ESWT with a gradually increasing energy protocol using both standard and novel trodes with an electrohydraulic generator in a randomized fashion. Noise reactivity and tolerance to treatment as measured in number of shocks and energy level achieved were recorded. Results Forty client-owned dogs with pathology affecting the hips, stifles, elbows, or shoulders were enrolled. Thirty-three dogs completed all three treatment sessions, three dogs completed two sessions, and four dogs completed one session. There was evidence of improved patient tolerability with the novel trode, based on an increased average number of shocks delivered (n ± SD = 848 ± 334 for novel trode; n ± SD = 767 ± 358 for standard trode; p = 0.0384) and higher average treatment energy level achieved (E ± SD = 6.5 ± 2.5 for novel trode; E ± SD = 5.3 ± 2.8 for standard trode; p = <0.001). Decreased noise reactivity was found to be positively correlated with tolerability of shockwave treatment (energy level: p = 0.0168; number of shocks: p = 0.0097). Discussion Administration of electrohydraulic ESWT is feasible in select awake patients using a gradually increasing energy protocol, and the tested novel shockwave trode is better tolerated than the standard trode. Further studies are required to determine the efficacy of the novel trode, and if gradually increasing energy protocols are clinically equivalent to current standard protocols that employ a consistent energy level.